Perancangan mesin classifier dengan ukuran mikron untuk pemisahan dan penyaringan bahan baku semen - Wibawa, Barnabas Satria; Saleh, Arif Rahman; Taufik, Ikhwan (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
High-quality cement is a key factor in good infrastructure. The demand for cement increased rapidly from 54 million tons in 2012 to 84 million tons in 2017, due to the growing infrastructure sector. In 2022, domestic cement consumption increased by 7.6%. Based on this data, the essential need for cement is on the rise. One of the efforts to enhance cement production is by optimizing raw material processing to produce high-quality cement. The objective of this study is to design a vibrating screen classifier machine for processing raw cement materials. The use of this machine aims to separate and filter the particle sizes of raw materials that have been processed by the crusher, thus sorting the raw materials to the desired sizes. This machine utilizes carbon steel 1020 and 316 Stainless steel materials, then analyzes the structural strength of the machine frame. In this research, modeling is done using SolidWorks 2019 software, and Finite Element Analysis (FEA) is conducted using ANSYS 2022 software. Mathematical equations include machine element calculations, flow capacity, and applied loads. Static analysis performed includes Von mises stress, displacement, and safety factor. The analysis results indicate that the maximum Von mises stress value is 53,865 MPa, the maximum total deformation is 2,1649 mm, and the safety factor minimum is 4,6804 above 3, confirming that the designed classifier machine is considered as safe.